Semantics Analysis of Slang (SAOS) in Social Media of Millennial Generation - Rezeki, Tri Indah; Sagala, Rakhmat Wahyudin (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2019)
Generation were born in every era eventually create their own language not least the latest generation commonly called the millennial generation. Specifically, the aim of our work broadens current knowledge of the phenomenon of Semantics Analysis of Slang (SAOS) in Social Media of Millennial Generation. This study investigated: 1) the types of SAOS used by millennial generation in social media; 2) how the meaning of SAOS used by millennial generation in social media; 3) why millennial generation used SAOS in social media.  This study applied descriptive qualitative research in order to reveal the data from the discourse of English Department students at Universitas Islam Negeri Sumatera Utara in social media such as Facebook and Instagram and it was obtained from observation, interview and documentation. The data showed that millennial generation used slang language in their communication in social media namely 33 slang languages in Facebook and 31 slang languages in Instagram. These languages consisted of five types of slang; fresh and creative; flippant; imitative; acronym; and clipping. The millennial generation used SAOS in their social media because some reasons such as to address, to initiate relax conversation, to express impression and to show intimacy.     Keywords: Slang, Types of slang, Reasons of slang, millennial generation